Comparison of performance of various leg-kicking techniques in fin swimming in terms of achieving the different goals of underwater activities - Rejman, M.; Siemontowski, P.; Siemienski, A. (PLOS ONE, 2020)
The aim of this study was to compare underwater fin swimming performance using dolphin, flutter and breaststroke kicks with and without diving gear. Performance was evaluated in terms of average swimming velocity. The parameters of spatiotemporal structure of the stroke reflecting to the swimming economy were employed. Conscious modifications in propulsion technique were considered here with the aim of controlling swimming performance. A total of ten professional scuba divers swam at maximal speed underwater for 50m using each of three techniques: dolphin, flutter, or breaststroke kicks. Swimmers` performance was compared between holding their breath and using breathing apparatus. Two cameras recorded their movements in sagittal and transverse planes. The average swimming velocity (vav), stroke length (SL), stroke rate (SR), index of variation of intracycle velocity (VIVIndex) and stroke index (SI) were estimated. Relative to the other techniques, the dolphin kick without a diving gear demonstrated the highest vav and low SI and VIVIndex values, which reflects the most advantageous economy of propulsion at given velocity. Given the lack of statistical differences, using the breaststroke kick and flutter kick when swimming with a diving gear seems to be comparable to dolphin-kick in terms of average velocity and parameters reflecting the economy of propulsion. Thus, a search for fin swimming techniques with the aim of achieving specific goals seemed reasonable. The results suggest, that performance achieved while using various fin swimming techniques was probably controlled by different strategies of leg movements. These strategies revealed differences in a spatiotemporal (SR-SL) structure of the stroke and they were closely associated in terms of the velocity variation decrease.